Isolation and Sequence Analyses of Salinity Tolerance Genes from Bruguiera Cylindrica (L.) Blume - Wong, Yeen Yee (2005)
Salinity is a major abiotic stress limiting the productivity of crop plants globally. The discovery of novel genes in stress adaptation will provide effective genetic engineering strategies leading to g reater stress tolerance. The objectives of this research are to identify and isolate salinity tolerance genes from the mangrove plant, Bruguiera cylindrica (L.) Blume through suppression subtractive hybridization (SSH) and bacterial functional assay. B. cylindrica propagules were grown in fresh water and 20 ppt salinity water. Root morphology differences between B. cylindrica grown in fresh water and 20 ppt salinity water were largely due to the need of roots to obtain more water and nutrients during salinity stress. B. cylindrica plants grew better in the presence of salt as higher mean values were obtained for all morphological measurements compared to B. cylindrica plants grown in fresh water. Four RNA extraction methods were attempted to obtain high yield and high purity RNA. The cesium chloride method was chosen for RNA extraction as it gave the highest amount of pure RNA. Subtracted cDNAs were prepared from the roots of the B. cylindrica seedlings that were grown in fresh water and salt water, respectively. A total of 84 subtracted cDNAs were cloned into pCR-BLUNT II TOPO and sequenced. A total of 51 subtracted cDNAs with good sequencing quality were assembled into 7 contigs and 10 singletons. These non-redundant sequences were grouped into unknown protein (41.18%), novel (29.41%), protein destination and storage (11.76%), energy (5.88%), intracellular traffic (5.88%) and protein synthesis (5.88%). Some motifs of novel and unknown sequences may involve in the salinity tolerance of B. cylindrica such as Kv1.3 voltage-gated K+ ion(s) channel signature, calcium-activated BK potassium channel alpha subunit and Kir2.1 inward rectifier K+ ion(s) channel signature. Meanwhile, a cDNA library was also constructed from the roots of B. cylindrica that were grown in fresh water. Bacterial functional assay was performed to identify cDNAs that confer salt tolerance. A total of 85 cDNA clones that were able to grow on 2x YT containing 400 mM NaCI were sequenced and 73 cDNAs with good sequence quality were assembled into 9 contigs and 53 singletons. The non-redundant sequences were also categorised into unknown protein (58.06%), metabolism (9.68%), transporters (9.68%), transcription (6.45%), energy (4.84%), cell growth/division (4.84%), novel (3.23%), miscellaneous (1.61%) and disease/defense (1.61%) A motif search on novel and unknown cDNAsequences had revealed some possible motifs that may be involved in salinity tolerance of B. cylindrica e.g. C. elegans Srg family integral membrane protein signature and 2Fe-2S ferredoxins, iron-sulfur binding region signature. Sequence analysis of subtracted cDNAs and putative salt tolerant cDNAs isolated by bacterial functional assay showed some putative proteins that may be involved in the salinity tolerance of B. cylindrica such as putative potassium transporter HAK 1p (M33), putative zinc finger protein (M3), ubiquitin (BC27) and L-ascorbate peroxidase (A46).